2009
DOI: 10.1097/brs.0b013e31819b061c
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Disc Replacement in Patients With and Without Previous Adjacent Level Fusion Surgery

Abstract: Although the level adjacent to a prior cervical fusion is subject to increased biomechanical forces, potentially leading to a higher risk of failure, the PCM disc was well tolerated in the short term. The early clinical results of disc replacement adjacent to a prior fusion are good and comparable to the outcomes after primary disc replacement surgery. However, in view of the small study population and short-term follow-up, continued study is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 38 publications
1
34
0
4
Order By: Relevance
“…The inclusion/exclusion age range was 18-60 years. The common indications and contraindications were similar to those used in other US IDE clinical studies [3,26]. Postoperatively, patients were mobilized with a soft-collar for 3 days under surveillance of a physical therapist.…”
Section: Patient Samplementioning
confidence: 99%
“…The inclusion/exclusion age range was 18-60 years. The common indications and contraindications were similar to those used in other US IDE clinical studies [3,26]. Postoperatively, patients were mobilized with a soft-collar for 3 days under surveillance of a physical therapist.…”
Section: Patient Samplementioning
confidence: 99%
“…Primer ve füzyon sonrası gelişen KSH'nı takiben yapılan artroplastilerin kısa dönem sonuçlarının karşılaştırıldığı serilerde, her iki grup arasında benzer klinik sonuçlar bulunmuştur. [26,27] Tablo 1. KSH etiyolojisinde risk faktörleri …”
Section: Servi̇kal Di̇sk Artroplasti̇si̇ (Sda) Ve Komşu Segment Hastaliğiunclassified
“…Benefits in terms of stresses reduction on adjacent segments may be more important for multilevel procedure than for mono-segmental surgery considering that loss of mobility is greater when multiple segments are fused. Recently, some authors reported clinical experience of TDR inserted at two levels or above previous fusion [20][21][22] and their results suggested that clinical outcomes after multilevel TDR were at least as good as those observed for single-level TDR. Although multilevel TDR could be an attractive option to treat multilevel cervical disc disease, there is still no consensus about the different treatment options: multilevel ACDF, multilevel TDR or hybrid constructs (arthrodesis combined with TDR).…”
Section: Introductionmentioning
confidence: 99%